FINANCIAL RISK ANALYSIS FOR INCREASING FINANCIAL PERFORMANCE OF SHARIA BANKS IN INDONESIA - Maya - Indriastuti; Chrisna Suhendi (Universitas Mercu Buana, 2021)
This study examined the effect of Islamic corporate governance on financial performance using financing risk as mediation, focusing on Sharia Banks in Indonesia. The researchers applied a multiple regression analysis on data collected from annual reports of the companies from 2013 to 2018. The Islamic corporate governance variable is calculated from the self-assessment of the Islamic corporate governance implementation in Sharia Banks. Meanwhile, the financial performance of Islamic banks is illustrated by the return on assets. Financing risk is measured by the ratio of non-performing financing. This study found that Islamic corporate governance cannot increase financial performance, but Islamic corporate governance can reduce financing risk. The decrease in financing risk can improve the financial performance of Sharia Banks, so it can be said that the financing risk variable can mediate the effect of Islamic corporate governance on financial performance.